Topographic factors drive plant diversity to a greater extent than vegetation structure in dry woodlands dominated by Ramorinoa girolae Speg - Campos Valeria Evelín; Gatica Gabriel (Flora, 2026)

Unprecedented mortality induced by extreme hot-drought in commercial planted Pinus spp stands is locally modulated by soil characteristics - Gabriel Gatica; Javier E. Gyenge; Nardia María Luján Bulfe; Norberto Pahr; Fernando Dalla Tea; María Elena Fernández (New Forests, 2024)

Spatio-temporal linkage variations between NDVI and tree rings on the leeward side of the northern Patagonian Andes - Verónica B. Gallardo; Martín A. Hadad; Fidel A. Roig; Gabriel Gatica; Feng Chen (Forest Ecology and Management, 2024)

Change of soil carbon storage in monoculture tree plantations across wide environmental gradients: Argentina as a case study - Javier Gyenge; Gabriel Gatica; Martín Sandoval; Ana María Lupi; Matías Gaute; María Elena Fernández; Pablo Luis Peri (Forest Ecology and Management, 2024)

Land Surface Temperature in an Arid City: Assessing Spatio-temporal Changes - Valeria E. Campos; Gabriel Gatica; Natalia Andino; Viviana N. Fernández Maldonado; Adriana Cardús (Remote Sensing in Earth Systems Sciences, 2023)

A posteriori error analysis of a Banach spaces-based fully mixed FEM for double-diffusive convection in a fluid-saturated porous medium - Sergio Caucao; Gabriel N. Gatica; Juan P. Ortega (Computational Geosciences, 2023)

Livestock settlement affects shrub abundance via plant functional diversity but not species richness in arid environments - Gabriel Gatica; Adrián Escudero; Eduardo Pucheta (Plant Ecology, 2020)

Environmental and anthropogenic drivers of soil methane fluxes in forests: Global patterns and among‐biomes differences - Gabriel Gatica; María E. Fernández; Maria P. Juliarena; Javier Gyenge (Global Change Biology, 2020)
Forest soils are the most important terrestrial sink of atmospheric methane (CH 4 ). Climatic, soil and anthropogenic drivers affect CH 4 fluxes, but it is poorly known the relative weight of each driver and whether all drivers have similar effects across forest biomes. We compiled a database of 478 in situ estimations of CH 4 fluxes in forest soils from 191 peer‐reviewed studies. All forest biomes (boreal, temperate, tropical and subtropical) but savannahs act on average as CH 4 sinks, which presented positive fluxes in 65% of the sites. Mixed effects models showed that combined climatic and edaphic variables had the best support, but anthropogenic factors did not have a significant effect on CH 4 fluxes at global scale. This model explained only 19% of the variance in soil CH 4 flux which decreased with declines in precipitation and increases in temperature, and with increases in soil organic carbon, bulk density and soil acidification. The effects of these drivers were inconsistent across biomes, increasing the model explanation of observed variance to 34% when the drivers have a different slope for each biome. Despite this limited explanatory value which could be related to the use of soil variables calculated at coarse scale (~1 km), our study shows that soil CH 4 fluxes in forests are determined by different environmental variables in different biomes. The most sensitive system to all studied drivers were the temperate forests, while boreal forests were insensitive to climatic variables, but highly sensitive to edaphic factors. Subtropical forests and savannahs responded similarly to climatic variables, but differed in their response to soil factors. Our results suggest that the increase in temperature predicted in the framework of climate change would promote CH 4 emission (or reduce CH 4 sink) in subtropical and savannah forests, have no influence in boreal and temperate forests and promote uptake in tropical forests.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Human impacts and aridity differentially alter soil N availability in drylands worldwide - Manuel Delgado‐Baquerizo; Fernando T. Maestre; Antonio Gallardo; David J. Eldridge; Santiago Soliveres; Matthew A. Bowker; Ana Prado‐Comesaña; Juan Gaitán; José L. Quero; Victoria Ochoa; Beatriz Gozalo; Miguel García‐Gómez; et al. (Global Ecology and Biogeography, 2016)
Aims Climate and human impacts are changing the nitrogen ( N ) inputs and losses in terrestrial ecosystems. However, it is largely unknown how these two major drivers of global change will simultaneously influence the N cycle in drylands, the largest terrestrial biome on the planet. We conducted a global observational study to evaluate how aridity and human impacts, together with biotic and abiotic factors, affect key soil variables of the N cycle. Location Two hundred and twenty‐four dryland sites from all continents except A ntarctica widely differing in their environmental conditions and human influence. Methods Using a standardized field survey, we measured aridity, human impacts (i.e. proxies of land uses and air pollution), key biophysical variables (i.e. soil pH and texture and total plant cover) and six important variables related to N cycling in soils: total N , organic N , ammonium, nitrate, dissolved organic:inorganic N and N mineralization rates. We used structural equation modelling to assess the direct and indirect effects of aridity, human impacts and key biophysical variables on the N cycle. Results Human impacts increased the concentration of total N , while aridity reduced it. The effects of aridity and human impacts on the N cycle were spatially disconnected, which may favour scarcity of N in the most arid areas and promote its accumulation in the least arid areas. Main conclusions We found that increasing aridity and anthropogenic pressure are spatially disconnected in drylands. This implies that while places with low aridity and high human impact accumulate N , most arid sites with the lowest human impacts lose N . Our analyses also provide evidence that both increasing aridity and human impacts may enhance the relative dominance of inorganic N in dryland soils, having a negative impact on key functions and services provided by these ecosystems.

Remote sensing variables as predictors of habitat suitability of the viscacha rat (Octomys mimax), a rock-dwelling mammal living in a desert environment - Valeria E. Campos; Gabriel Gatica; Laura M. Bellis (Mammal Research, 2015)